2020
DOI: 10.3389/fpsyg.2020.00462
|View full text |Cite
|
Sign up to set email alerts
|

Visual Processing Matters in Chinese Reading Acquisition and Early Mathematics

Abstract: The main purpose of the present study was to investigate whether visual processing uniquely contributed to character reading and early mathematics in Chinese children. Eighty-two Chinese kindergarteners at K3 (mean age = 68 months, SD = 0.30) were followed up to grade one (mean age = 82 months, SD = 0.35) with an interval of 14 months. Nonverbal intelligence, inhibitory control, sustained attention, character reading, and mathematics were measured at kindergarten. Character reading and mathematics were assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 87 publications
6
11
1
Order By: Relevance
“…Specifically, verbal working memory, rather than visuospatial working memory, explained the unique variance in children's learning of character reading. These findings were consistent with those cross‐sectional studies revealing that character reading was associated with visual skills (Li et al, 2012) and some longitudinal research showing that visual skills (X. Yang & Meng, 2020) and working memory (Aguilar‐Vafaie, Safarpour, Khosrojavid, & Afruz, 2012) significantly predicted word recognition. Our study further confirmed that the influences of visual skills and verbal working memory in Chinese reading were independent of children's age, gender, inhibitory control, decision speed, and attention.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Specifically, verbal working memory, rather than visuospatial working memory, explained the unique variance in children's learning of character reading. These findings were consistent with those cross‐sectional studies revealing that character reading was associated with visual skills (Li et al, 2012) and some longitudinal research showing that visual skills (X. Yang & Meng, 2020) and working memory (Aguilar‐Vafaie, Safarpour, Khosrojavid, & Afruz, 2012) significantly predicted word recognition. Our study further confirmed that the influences of visual skills and verbal working memory in Chinese reading were independent of children's age, gender, inhibitory control, decision speed, and attention.…”
Section: Discussionsupporting
confidence: 91%
“…The present study revealed the significant contributions of visual skills to Chinese character reading among kindergarten children. This finding confirmed the results of another study of mainland Chinese young children (X. Yang & Meng, 2020). Indeed, children with visual processing impairments usually demonstrated reading difficulties, and training visual skills would promote the reading performance of children with developmental dyslexia (Meng, Cheng‐Lai, Zeng, Stein, & Zhou, 2011).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Chinese semantic‐phonetic character compounding typically positions the semantic component to the left of the phonetic, but this component can also appear above, below, after, or surrounding the phonetic. Learning the many positional regularities (and exceptions) of a script appears to tax visuospatial skills (McBride, 2016; Yang & Meng, 2020), a factor that the science of reading has concluded is unimportant in English reading (Vellutino, Fletcher, Snowling, & Scanlon, 2004).…”
Section: Embracing Global Diversity: Toward a Global Nonethnocentric Science Of Readingmentioning
confidence: 99%